Interpersonal Communication Strategies for Building Customer Trust at Informa Elektronik Suncity Sidoarjo: Strategi Komunikasi Interpersonal Membangun Kepercayaan Pelanggan pada Informa Elektronik Suncity Sidoarjo - Al’Azmi, Moch Neezarth; Dharma, Ferry Adhi (Universitas Muhammadiyah Sidoarjo, 2025)
Background: In the competitive electronic retail industry, building customer trust is crucial. This study addresses the need to understand how interpersonal communication strategies contribute to this trust-building process, specifically at Informa Elektronik Suncity Sidoarjo. Knowledge Gap: Existing research lacks a detailed examination of the specific interpersonal communication techniques employed by salespersons and their direct influence on customer loyalty and sales in this particular context. Aims: This research aims to analyze the interpersonal communication strategies used by Informa Elektronik Suncity Sidoarjo sales staff to build customer trust. Results: Findings reveal that the applied strategies align with DeVito's theory, incorporating openness, empathy, support, positive attitude, and equality. Practical strategies, such as mastering product knowledge, offering after-sales services, and leveraging digital media, were found to enhance customer loyalty and strengthen the company's image. Novelty: This study uniquely demonstrates the direct link between the application of DeVito’s interpersonal communication principles and tangible business outcomes within a specific retail setting. Implications: The research confirms that effective interpersonal communication is a key factor in establishing mutual trust between a company and its customers. Highlights : The study identifies interpersonal communication strategies (openness, empathy, support) aligned with DeVito's theory. Applying these strategies, along with product knowledge and after-sales service, increases customer loyalty and company image. Effective interpersonal communication is a crucial factor for building customer trust and achieving sales targets in a competitive retail environment. Keywords: Interpersonal Communication, Customer Trust, Retail Strategy, Customer Loyalty, Salesmanship